2004
DOI: 10.1063/1.1646750
|View full text |Cite
|
Sign up to set email alerts
|

Charge storage and photoluminescence characteristics of silicon oxide embedded Ge nanocrystal trilayer structures

Abstract: Metal-oxide-semiconductor capacitors with a trilayer structure consisting of the cap gate oxide, sputtered SiGe layers and thermally grown tunnel oxide were fabricated on p-Si substrates. The trilayer structures were rapid thermal annealed at 1000 °C in nitrogen atmosphere for different durations. Cross-sectional transmission electron micrographs revealed the complete isolation of Ge nanocrystals in the sandwiched structure annealed for a longer duration. The optical and charge storage characteristics of trila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 18 publications
0
43
0
1
Order By: Relevance
“…Ge nanocrystals embedded in SiO 2 have attracted a strong interest in the scientific community due to their potential applications in optoelectronics as light emitters, and in highspeed, low-power logic and memory devices [1,2]. A promising way to synthesize Ge nanocrystals within a SiO 2 matrix film is by high-temperature annealing of SiO 2 /a-Ge/SiO 2 trilayer structures [3].…”
Section: Introductionmentioning
confidence: 99%
“…Ge nanocrystals embedded in SiO 2 have attracted a strong interest in the scientific community due to their potential applications in optoelectronics as light emitters, and in highspeed, low-power logic and memory devices [1,2]. A promising way to synthesize Ge nanocrystals within a SiO 2 matrix film is by high-temperature annealing of SiO 2 /a-Ge/SiO 2 trilayer structures [3].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Ge-NC memory structures are strongly influenced by defect states at such interfaces in addition to effects due to the NCs. [8][9][10][11] It has been reported that ion implantation of Ge into thin SiO 2 layers on Si wafers, followed by annealing, results in Ge accumulation at the Si/ SiO 2 interface. [12][13][14] Diffusion of Ge atoms during annealing can alter the interface, thereby having a significant influence on the memory characteristics of such structures.…”
Section: J H Han and Chungwoo Kimmentioning
confidence: 99%
“…Most studies have focused on the fabrication on Si and Ge nanocrystals in metal-oxidesemiconductor (MOS) structure [12][13][14][15][16][17][18][19][20]. In addition, atomicforce-microscopy (AFM) was utilized to inject charges in the nanocrystals [21][22][23].…”
Section: Nanocrystals Structurementioning
confidence: 99%